Initial development of Physalis seedlings in substrates and containers - Villa, Fabíola; Silva, Daniel Fernandes da; Peron, Thiago Augusto; Mezzalira, Éder Junior (Federal University of Piauí, 2018)
The objective of this study was to evaluate the growth of Physalis peruviana and Physalis pubescens in containers and substrates, as well as the growth of transplanted P. pubescens seedlings into different containers and substrates. It was used for transplanting experiment (E1) plastic bags, disposable plastic glasses and plastic tubes containing four substrates: oxisol; commercial substrate; commercial substrate + fine washed sand; and commercial substrate + oxisol + fine washed sand. For the experiment of containers x substrates (E2) it was used polystyrene and polypropylene trays, both with 200 cells containing two substrates: vermiculite + commercial substrate and vermiculite + oxisol. For the experiment of containers x substrates (E3), it was used polystyrene trays with 128 and 200 cells and plastic tubes containing four substrates: commercial substrate, oxisol, fine washed sand, oxisol + fine washed sand and oxisol + fine washed sand + commercial substrate. The experimental design used in E1, E2 and E3 was randomized blocks in factorial 3x4, 2x2, and 3x5, respectively, containing 4 replicates and 10 plants per plot. The use of commercial substrate Húmus Fértil® for P. pubescens seedlings transplanted from seedbed to containers such as plastic glasses or plastic bags provides better seedling growth. For Physalis peruviana, better results are verified in the use of polypropylene tubes containing washed fine sand + commercial substrate Húmus Fértil® + oxisol or washed fine sand + oxisol. Better results for formation of P. pubescens seedlings were verified by using expanded polystyrene trays containing oxisol + vermiculite mixture.